2010
DOI: 10.1515/cclm.2011.016
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone is an independent determinant of bone mineral density in men with type 2 diabetes mellitus

Abstract: Our data indicate that androgens are independent determinants of BMD in male patients with DT2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
1
1
0
1
Order By: Relevance
“…In males, free testosterone, SHBG and total testosterone were different with regard to correlation with BMD in most studies. [20][21][22] Similar results were found in females. 23 We speculated that total testosterone and estradiol used in the current study may partially explain the differences in our findings from other studies.…”
Section: Discussionsupporting
confidence: 83%
“…In males, free testosterone, SHBG and total testosterone were different with regard to correlation with BMD in most studies. [20][21][22] Similar results were found in females. 23 We speculated that total testosterone and estradiol used in the current study may partially explain the differences in our findings from other studies.…”
Section: Discussionsupporting
confidence: 83%
“…It is not completely clear whether duration of T2DM is associated with BMD. Some studies did not found an association between BMD and duration of the disease [53][54][55], but others did show a negative association [56][57][58][59]. As the studies that were not able to find an association between BMD and duration of the disease did not include any patients with a very long duration (>20 years) of the disease, the lack between an association between BMD and duration of the disease in this studies could be due to population bias.…”
Section: Bone Massmentioning
confidence: 70%
“…Un estudio realizado en 138 diabéticos tipo 2 mostró que las concentraciones de TL se asociaban directamente con la DMO en miembros superiores y costillas pero no con la de la columna, la cadera, ni con la DMO global (341). Otro trabajo reciente observó correlación significativa entre la TT y TL con la DMO de la columna lumbar y demostró que la TT era un determinante independiente de la DMO en varones con DM tipo 2 (347). Está por determinar la influencia que pueden tener las concentraciones de estradiol sobre la DMO en este grupo de pacientes, ya que los varones con hipogonadismo generalmente tienen concentraciones de estradiol más bajas, debido a que la testosterona es el sustrato para la formación de estradiol (105), y en algunos estudios las concentraciones de estradiol se han relacionado, de forma más robusta que la testosterona, con la DMO en varones (348).…”
Section: Densidad óSeaunclassified